Mental Health Education for Pregnant Women during the COVID-19 Pandemic in Surakarta, Indonesia - Widyawati Widyawati; Fatwa Sari Tetra Dewi; Yuli Kusumawati (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
The main factors increasing the risk of depression are pregnant women’s lack of knowledge about recognizing signs and symptoms, early detection, and prevention efforts. The purpose of this study is to examine the impact of mental health education on pregnant Indonesian women’s knowledge and self-efficacy during the COVID-19 pandemic. A quasi-experimental study was conducted. Pregnant women in four Surakarta primary health care facilities received antenatal care using Basic Emergency Obstetric Neonatal Care. The inclusion criteria for the sample were 127 pregnant women with a gestational age of 24-36 weeks, no family history of mental disorders, a singleton pregnancy, and participation in the intervention from beginning to end. The study excluded pregnant women who experienced complications during their pregnancy. Sample sizes for the intervention and control groups were 67 and 60 pregnant women, respectively. Personal psychoeducation intervention was provided by trained midwives during antenatal care. During the intervention, materials were presented in modules, and videos were shared through WhatsApp groups and discussions. The Edinburgh Postpartum Depression Scale was used to assess depressive symptoms. The data were analyzed using the paired t-test and independent t-test. Following the intervention, the mean score for knowledge and self-efficacy increased. Depressive symptom scores decreased following the intervention and were significantly different from the control group. Mental health education interventions for pregnant women using modules and videos can improve pregnant women’s knowledge and self-efficacy in preventing antenatal and postnatal depression.